Q: What is the result if you divide -12x8 y8 by 3x4 y2?

Write your answer...

Submit

Related questions

6x5y5

y2=-x2-8x+6

(y2+13y+22)/(y+2) = (y+11)

-12 x8 y8 / 3x4 y2 = -4 x4y6 First: divide -12 by 3 which equals -4 Second: divide x to the power of 8 by x to the power of 4 by subtracting the two powers ( 8-4 ) which will equal x to the power of 4 Third: divide y to the power of 8 by y to the power of 2 by subtracting the two powers ( 8-2 ) which will equal y to the power of 6

y-1/y2-y+1=y/y-1

y2 + y2 = 2y2

4x-y2 = 2

y2=26 y2/2 l 26/2 y = 13 when using " 4 line method", the purpose is to isolate the variable. the coefficent states that you're multiplying y by 2, so to isolate the variable, you have to get rid of the 2, which you do by dividing y2 by 2. likewise, if the equation stated y+2, to isolate the variable, you subtract 2. it works the other way aroind, too. if the equation stated y/2, to isolate the variable, you multiply it by 2. the same thing with y-2. you add 2. now, the division property of equality states that when you divide on the left, you divide on the right, too. so when you divide y2 by 2 in order to isolate the variable, you have to divide 26 by 2 as well, giving you your answer of y+13. class is dismissed. ;3

y6 x y2 y4 x y4 y2 x y2 x y4 y2 x y2 x y2 x y2

0

(x-2)^2+y^2=64

The formula: distance=sqrt(((x1-x2)*(x1-x2))+((y1-y2)*(y1-y2))+((z1-z2)*(z1-z2))) In DarkBASIC it's: function distance3D(x1,y1,z1,x2,y2,z2) x=x1-x2 y=y1-y2 z=z1-z2 result=sqrt((x*x)+(y*y)+(z*z)) endfunction result In classic BASIC I think it's: FUNCTION distance3D(x1,y1,z1,x2,y2,z2) x=x1-x2 y=y1-y2 z=z1-z2 result=SQRT((x*x)+(y*y)+(z*z)) RETURN result END FUNCTION

y2 there will me many solutions

It is: y2

The expression Y-2 is 1/Y2. The reciprocal of 1/Y2 is Y2.

There is no expansion for x2 + y2

88 + 5y - y2 66 - 3y + y2 Subtract: 22 + 8y -2y2

y2

Yes, as x-y2=0

1 m2 = 1.196 y2 approx.

x2 + 2x + y2 = 12 (complete the square)(x2 + 2x + 1)+ y2 = 12 + 1(x + 1)2 + y2 = 13 (divide by 13 each element to both sides)(x + 1)2/13 + y2/13 = 1(x - -1)2/13 + (y - 0)2/13 = 1Thus, the center of the circle is (-1, 0) and its radius is 1.

4 - y2 can be written as 22 - y2. This has become of the form of x2 - y2.Expansion for x2 - y2 is (x+y)(x-y).So, 4 - y2 = 22 - y2 = (2+y)(2-y)

4x2-y2 = (2x-y)(2x+y)

The GCF is y2.

What do you want to convert it to? x2 + y2 = 2x If you want to solve for y: x2 + y2 = 2x ∴ y2 = 2x - x2 ∴ y = (2x - x2)1/2 If you want to solve for x: x2 + y2 = 2x ∴ x2 - 2x = -y2 ∴ x2 - 2x + 1 = 1 - y2 ∴ (x - 1)2 = 1 - y2 ∴ x - 1 = ±(1 - y2)1/2 ∴ x = 1 ± (1 - y2)1/2

Study guides